2017 International Conference on Rehabilitation Robotics (ICORR) 2017
DOI: 10.1109/icorr.2017.8009455
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in using compliant ligaments for position estimation within robotic joints

Abstract: Abstract-The mechanical advantages of bio-inspired condylar robotic knee joints for use in prosthetics or rehabilitation has been argued extensively in literature. A common limitation of these designs is the difficulty of estimating joint angle and therefore accurately controlling the joint. Furthermore, the potential role of ligament-like structures in robotic knees is not very well established. In this work, we investigate the role of compliant stretch sensing ligaments and their integration into a condylar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…For this reason the joint was manipulated by hand. Although previous work on an earlier version of the joint suggests that these forces are likely to have an effect on the ligament stretch [24] the effect of these forces on the centre of rotation and moment arm is not known. A full investigation of how these loads move the centres of rotation and how this effects joint performance will be a matter for future work.…”
Section: Test Proceduresmentioning
confidence: 97%
See 2 more Smart Citations
“…For this reason the joint was manipulated by hand. Although previous work on an earlier version of the joint suggests that these forces are likely to have an effect on the ligament stretch [24] the effect of these forces on the centre of rotation and moment arm is not known. A full investigation of how these loads move the centres of rotation and how this effects joint performance will be a matter for future work.…”
Section: Test Proceduresmentioning
confidence: 97%
“…Specifically, we add elastic stretch sensing ligaments and a biologically derived condyle profile. Initial data from a prototype version of the joint has shown that stretch in compliant ligaments is a function of joint forces and angular velocity as well as joint position and could provide some sensory benefit [24]. The method presented here employs a computer model developed in MATLAB to generate a tibia joint surface profile given a number of inputs taken from cadaver studies.…”
Section: B Aims Of This Workmentioning
confidence: 99%
See 1 more Smart Citation
“…More physiologically driven studies [37], [38] implemented a robotic system based on condylar knee design with demonstrated mechanical benefits, though tendons or compliance were not directly investigated. Our own work on human-like knee joints [39]- [41] explored similar issues for the purpose of designing new joints for walking robots or exoskeletons. The patella was simplified as a bracket attached to the tibia or pulley attached to the femur in those studies.…”
Section: A Related Workmentioning
confidence: 99%
“…The design presented here goes further by including elastic stretch sensing ligaments and a biologically derived condyle shape. In our previous work [33] a design for stretch sensing compliant ligaments and a condylar knee was presented. Using this first iteration of the joint we show that stretch in these ligaments is a function of joint forces and angular velocity as well as joint position.…”
Section: Work To Datementioning
confidence: 99%